Psuedosymmetry and pseudomerodry or nonmerohedral twinning for the known structure of diaquabis(quinolin‐8‐olato‐κ2N, O)zinc(II). (28th August 2013) - Varelas, Georgios; Salifoglou, Athanasios; Psycharis, Vassilis
<x xml:space="preserve">Abstract</x> The structure of the title centrosymmetric compound, [Zn(C9H6NO)2(H2O)2], has already been solved three times [Merritt, Cady & Mundy (1954). Acta Cryst.7, 473–476; Palenik (1964). Acta Cryst.17, 696–700; Chen, Zhang, Shi, Huang, Liang & Zhou (2003). Acta Cryst. E59, m814–m815]. The authors of the two most recent papers state that they attained lower R1 values than that obtained in the 1954 paper, but they do not mention that Merritt et al. had derived the structural model from a twinned crystal. Also, from a structural point of view, there are strong indications that the most recent report is in fact the isostructural CuII complex already reported by Okabe & Saishu [Acta Cryst. (2001), E57, m251–m252] and not the ZnII complex. The structure of the title compound is reported here based on data obtained from a twinned crystal.